Evolution of Centromeric Retrotransposons in Grasses - Sharma, Anupma (Oxford University Press, 2014)
Centromeric retrotransposons (CRs) constitute a family of plant retroelements, some of which have the ability to target their insertion almost exclusively to the functional centromeres. Our exhaustive analysis of CR family members in four grass genomes revealed not only horizontal transfer (HT) of CR elements between the oryzoid and panicoid grass lineages but also their subsequent recombination with endogenous elements that in some cases created prolific recombinants in foxtail millet and sorghum. HT events are easily identifiable only in cases where host genome divergence significantly predates HT, thus documented HT events likely represent only a fraction of the total. If the more difficult to detect ancient HT events occurred at frequencies similar to those observable in present day grasses, the extant long terminal repeat retrotransposons represent the mosaic products of HT and recombination that are optimized for retrotransposition in their host genomes. This complicates not only phylogenetic analysis but also the establishment of a meaningful retrotransposon nomenclature, which we have nevertheless attempted to implement here. In contrast to the plant-centric naming convention used currently for CR elements, we classify elements primarily based on their phylogenetic relationships regardless of host plant, using the exhaustively studied maize elements assigned to six different subfamilies as a standard. The CR2 subfamily is the most widely distributed of the six CR subfamilies discovered in grass genomes to date and thus the most likely to play a functional role at grass centromeres.